2010
DOI: 10.1007/s10637-010-9528-x
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of oral irinotecan as a single-agent and given sequentially with capecitabine

Abstract: Oral irinotecan can be safely administered as a single agent or in sequential combination with capecitabine. The efficacy of oral irinotecan should be explored further as a potentially convenient alternative to IV chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
3
9
0
Order By: Relevance
“…Previously, we have demonstrated the efficacy of intravenous systematic nanovesicle TUSC2 gene delivery in NSCLC mouse models [4]-[7]. To validate the antitumor activity of TUSC2-MK2206 in vivo , we evaluated the effect of this combination on inhibiting tumor growth in an LKB1-defective human H322 lung cancer xenograft mouse model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have demonstrated the efficacy of intravenous systematic nanovesicle TUSC2 gene delivery in NSCLC mouse models [4]-[7]. To validate the antitumor activity of TUSC2-MK2206 in vivo , we evaluated the effect of this combination on inhibiting tumor growth in an LKB1-defective human H322 lung cancer xenograft mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have demonstrated that exogenous expression of TUSC2 in non-small cell lung carcinoma cells, deficient of its expression, significantly inhibited tumor cell growth [5], [6]. In addition, intravenous systemic delivery of TUSC2 to distant tumors, via intravenous N-[1-(2,3-dioleoyloxy)propyl]-N,N,N-trimethylammonium chloride (DOTAP): cholesterol nanovesicles, suppressed tumor growth and progression in orthotopic human lung cancer xenograft models, and in a phase I clinical trial of stage 4 lung cancer patients who had progressed on chemotherapy [4]–[7].…”
Section: Introductionmentioning
confidence: 99%
“…They allow self-medication, flexibility in the dosing schedule and more importantly minimize the need for hospitalisation, hence dramatically reducing the cost of treatment [97]. The current limitations for oral delivery of SN38 are poor and erratic absorption (10-20% as oral CPT-11) and thus a variable therapeutic response [39,41,98]. Furthermore, the debilitating diarrhoea which is due to the free SN38 generated in the intestine during enterohepatic recirculation, and the limited drug absorption to the systemic circulation due to the intestinal metabolism by CYP enzymes during absorption and the P-gp efflux [26,27,44,99] also limit the oral delivery of SN38 or CPT-11 directly.…”
Section: Oral Delivery Of Sn38mentioning
confidence: 99%
“…Irinotecan, a topoisomerase I inhibitor was also selected as a probe compound because its metabolite SN‐38 is activated by a carboxyesterase pathway rather than CYP450, thereby providing data for supplement interaction with non‐CYP450 mediated activation pathways. The maximum tolerated oral dose for irinotecan as a single agent in patients with active solid tumour malignancies is 60 mg/m 2 per day …”
Section: Discussionmentioning
confidence: 99%
“…The maximum tolerated oral dose for irinotecan as a single agent in patients with active solid tumour malignancies is 60 mg/m 2 per day. [35] One difficulty in analysing the data from these experiments is that each supplement contains multiple inhibitors, functioning via different inhibition mechanisms, and these inhibitors are present over a broad range of concentrations in the supplement. Additionally, the composition of the components in the supplements may also vary as a function of product preparation or seasonal and geographical origin.…”
Section: Discussionmentioning
confidence: 99%